2013
DOI: 10.1002/phar.1240
|View full text |Cite
|
Sign up to set email alerts
|

Once‐Weekly Exenatide: An Extended‐Duration Glucagon‐Like Peptide Agonist for the Treatment of Type 2 Diabetes Mellitus

Abstract: Type 2 diabetes affects over 25 million people in the United States. There are many treatment options for patients with type 2 diabetes, but current treatments must be administered on a daily basis. Once-weekly exenatide, an extended-duration glucagon-like peptide-1 (GLP-1) agonist, provides an option for patients to take a drug weekly, with pharmacotherapeutic effects that are superior to twice-daily exenatide and sitagliptin and comparable to insulin glargine. The DURATION trials provide evidence that once-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Long-acting exenatide is formulated in microspheres of poly-(d,l-lactide- co -glycolide) for once-weekly administration [19]. Liraglutide is another long-acting GLP-1RA that is administered once daily.…”
Section: Structure and Physiology Of Glucagon-like Peptide-1 (Glp-1)mentioning
confidence: 99%
“…Long-acting exenatide is formulated in microspheres of poly-(d,l-lactide- co -glycolide) for once-weekly administration [19]. Liraglutide is another long-acting GLP-1RA that is administered once daily.…”
Section: Structure and Physiology Of Glucagon-like Peptide-1 (Glp-1)mentioning
confidence: 99%
“…Exending is a GLP-1 peptide analogue discovered from the salive of guila monster, which display GLP-1 agonism pharmacologic effect, and currently marketed as a pos-prandial injection or a once-a-week or once-a-month formulation in polymeric microparticles (Liu et al, 2010;Minze et al, 2013;Pinelli and Hurren, 2011). An adverse reaction observed with exendin therapy is pancreatite (Aroda and DeYoung, 2011;Ryan et al, 2013a), and without the cardiovascular benefits observed with liraglutide.…”
Section: Introductionmentioning
confidence: 99%
“…Patients initiating OW GLP-1RAs, including semaglutide, were twice as likely to achieve all clinical outcomes of interest (HbA 1c and/or weight-loss goals) compared with those initiating DPP-4i. These outcomes from the comparator analysis are aligned with previous RCTs and real-world studies [ 19 , 26 – 29 ]. The DURATION-2 trial demonstrated greater mean HbA 1c reduction (− 1.5% vs. − 0.9%) and weight loss (− 2.3 kg vs. − 1.5 kg) in patients treated with exenatide OW compared with sitagliptin (a DPP-4i).…”
Section: Discussionmentioning
confidence: 64%